Article PENYULUHAN GAYA BERPAKAIAN ISLAMI KEPADA ANAK MELALUI KEGIATAN FASHION SHOW ANTAR PAUD SE-KECAMATAN MARANCAR - Pasaribu, Heka Afriannur (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
ABSTRACT Along with the development of the times, the world of fashion or fashion more and more new models and styles that come out. All fashion trends are competing to create fashion that is liked by the public. Apart from the world of fashion which is trending nowadays, we must pay attention to these modes so that we don't choose the wrong one, even to the point where there are those who violate the Islamic dress code. The purpose of this activity is to increase awareness of early childhood children to cover their nakedness since they are small. So that they get used to covering their genitals until they grow up. The result of this activity is that children are more motivated to pay attention to their appearance according to the teachings of the Islamic religion. know the limits of their private parts and can invite their friends to participate in covering their genitals as well by still dressing in Islamic fashion but not missing trendy fashions. Keywords: clothing, children, Islam